2020
DOI: 10.3390/cli9010006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Crop Production and Potential Adaptive Measures in the Olifants Catchment, South Africa

Abstract: Climate change is expected to substantially reduce future crop yields in South Africa, thus affecting food security and livelihood. Adaptation strategies need to be implemented to mitigate the effect of climate change-induced yield losses. In this paper, we used the WEAP-MABIA model, driven by six CORDEX climate change data for representative concentration pathways (RCPs) 4.5 and 8.5, to quantify the effect of climate change on several key crops, namely maize, soya beans, dry beans, and sunflower, in the Olifa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 39 publications
(47 reference statements)
2
22
0
Order By: Relevance
“…Effects of climate change in crops have also been studied previously in arid and semi-arid regions such as Jordan. Results agree with our findings, as increasing crop water requirements and steady decline in crop yields are expected, due to raising temperatures, increased evapotranspiration and decreased precipitation during planting seasons [38,39,41,46].…”
Section: No Intervention Scenariosupporting
confidence: 92%
See 1 more Smart Citation
“…Effects of climate change in crops have also been studied previously in arid and semi-arid regions such as Jordan. Results agree with our findings, as increasing crop water requirements and steady decline in crop yields are expected, due to raising temperatures, increased evapotranspiration and decreased precipitation during planting seasons [38,39,41,46].…”
Section: No Intervention Scenariosupporting
confidence: 92%
“…The MABIA-WEAP package (originally developed in the Institut National Agronomique de Tunisie by Dr. Ali Sahli and Mohamed Jabloun) [37] has been commonly used to project crop and irrigation water requirements and estimate the effects of climate change on crops [38,39]. We used MABIA to make daily simulations of evapotranspiration, irrigation needs and climatic and crop-specific variables.…”
Section: The Mabia Methodsmentioning
confidence: 99%
“…In addition to human and economic factors, environmental factors might have also largely contributed to the percentage of cropland cover and the crop production quantity during the study years (Figure 8), and this has been reported by several authors [116,117]. For example, the average precipitation was not uniformly distributed.…”
Section: Impacts Of Environmental Factors On Food Securitymentioning
confidence: 64%
“…To establish values for this parameter, yield data of the different crops were obtained from the Thuringian state statistics (TLS, 2021). The Yield Response Factor is a factor that describes the reduction in relative yield according to the reduction in the crop evapotranspiration (ETc) caused by soil water shortage (Olabanji et al, 2021). The data were obtained from the crop library functionality that is implemented in WEAP-MABIA and based on the FAO-56 report (Allen et al, 1998).…”
Section: Catchment Data: User Defined Parametersmentioning
confidence: 99%